"Heat from Cold" – A new cycle for upgrading the ambient heat: Adsorbent optimal from the dynamic point of view. (September 2017) - Aristov, Yuri I.
Highlights: Which adsorbent is optimal for the HeCol cycle from the dynamic point of view? Ideal adsorbent: a step-like isotherm with the step at the stage initial pressure. Real adsorbent: a concave isobar accelerates desorption; a convex isobar – adsorption. This analysis helps in selection of adsorbent dynamically optimal for the HeCol cycle. Abstract: A new adsorptive cycle has recently been suggested for upgrading a temperature potential of the ambient heat in cold countries (the so-called "Heat from Cold" or HeCol cycle). Because of the low operating temperature and pressure, a special attention has to be paid on dynamic aspects of the HeCol cycle. In this paper, we analyze which adsorbents are optimal for the HeCol cycle from the dynamic point of view. Appropriate recommendations are made.